A German survey of the abdominal transplantation surgical work force - Thomas, Michael Nikolaus; Nadalin, Silvio; Schemmer, Peter; Pascher, Andreas; Kaiser, Gernot Maximilian; Braun, Felix; Becker, Thomas; Nashan, Björn; Guba, Markus (Transplant international, 2015)
This manuscript reports the results of a nationwide survey of transplant surgeons in Germany, including the demographics, training, position, individual case loads, center volumes, program structure, professional practice, grade of specialization, workload, work hours, salary, and career expectations. We contacted all 32 German transplant centers that perform liver, kidney, and pancreas transplantation. Surgeons engaged in transplantation were asked to reply to the survey. Eighty-five surgeons responded, with a mean age of 44 ± 8 years, 13% of whom were female. The median transplant frequency per active transplant surgeon was relatively low, with 16 liver transplants, 15 kidney transplants, and three pancreas transplants. The median reported center volumes were 45 liver transplants, 90 kidney transplants, and five pancreas transplants per year. Most of the surgeons reported a primary focus on hepato-pancreato-biliary surgery, and only 10% of effective work time was actually dedicated to perform transplant surgeries. The majority of respondents estimated their weekly work hours to be between 55 and 66 h. When asked about their career satisfaction and expectations, most respondents characterized their salaries as inappropriately low and their career prospects as inadequate. This survey provides a first impression of the transplant surgery work force in Germany.